Філософське осмислення проблеми впровадження сучасних блокчейн технологій - Романенко, П. А. (ХНУРЕ, 2022)
The article considers the philosophical problems of the spread of popular digital blockchain technologies, distributed storage technologies. It is believed that this technology can be used to record and track any type of information: from medical indicators to political elections. Modern philosophy can not help but be interested in this phenomenon, because it has centuries of experience in considering abstract, intangible, absolute things, and plays an important role in understanding the nature of these technologies and their impact on society. Blockchain technologies are based on guarantees that data on the movement of data within the system cannot be changed
Keywords: блокчейн технології